Acrylic acid adsorption foam and foam tape
By forming a semi-open structure on the foam surface, the problem of not being easy to peel off in traditional foam is solved, and the easy peelability and good physical properties of foam are achieved.
Patent Information
- Application Number
- CN202411421679.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-25
AI Technical Summary
Traditional foam is not easy to peel off during the process, display and use of electronic products, resulting in inconvenience in the process.
Acrylic adsorption foam with an open-cell structure is prepared by chemical foaming method, and a release film or a peelable protective film of different grams of weight is covered on the surface to control the formation of bubbles overflowing on the foam surface to form a foam surface layer with a semi-cell structure.
It realizes the easy peelability of foam, while maintaining good impact resistance and cushioning properties, and is suitable for temporary fixation and reuse.
Smart Images

Figure BDA0005080993220000031 
Figure BDA0005080993220000041 
Figure BDA0005080993220000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of pressure-sensitive adhesive tapes, and in particular to a foam tape based on absorbable foam. Background Art
[0002] Foam is widely used in electronic products because of its good cushioning performance and compressibility. Foam materials can be divided into many types according to their materials and uses, including but not limited to PU foam, anti-static foam, conductive foam, EPE, anti-static EPE, CR, EVA, bridged PE, SBR, EPDM, etc. These foam materials have their own characteristics, such as elasticity, light weight, fast pressure-sensitive fixation, etc., and are widely used in various industries, such as electronics, automobiles, medical, etc. Different uses and locations have completely different requirements for foam.
[0003] During the manufacturing, display and use of electronic products, some parts need to be reworked or temporarily fixed, such as internal gaskets of electronic products, mobile phone displays, and mobile phone holders on aircraft. The peeling force increases significantly over a long period of time and in a complex environment, making it difficult to peel off, causing many inconveniences to the manufacturing process.
[0004] Acrylic resin is formed by copolymerization of acrylate, methacrylate and vinyl monomers such as styrene as the main raw materials. It has certain advantages in aging resistance. The difficulty of the chemical foaming process of acrylic resin lies in the control of bubble size. Usually, if the modulus of the material is too high, the bubbles will overflow and fail to form a regular bubble structure. If the modulus is too low, the bubbles will easily merge with each other to form larger bubbles, and the ideal state cannot be achieved.
[0005] It should be noted that the above introduction to the technical background is only for the convenience of providing a clear and complete description of the technical solutions of the present invention and for the convenience of understanding by those skilled in the art. It cannot be considered that the above technical solutions are well known to those skilled in the art simply because these solutions are described in the background technology section of the present invention. Summary of the invention
[0006] Purpose of the invention: The present invention provides an acrylic adsorption foam, which solves the problem that traditional foam is difficult to peel off and causes many inconveniences in the manufacturing process.
[0007] Technical solution: The acrylic absorbent foam of the present invention has an open-pore structure on at least one surface thereof. Preferably, the open-pore structure is a semi-open-pore structure.
[0008] The preparation method of acrylic adsorption foam comprises the steps of using a foaming mixed glue solution containing an acrylic resin solution as a foaming base material and preparing the adsorption foam by a chemical foaming method, wherein before the chemical foaming, the step of coating the foaming mixed glue solution on a peelable protective film is also included.
[0009] Preferably, the peelable protective film is a PET release film.
[0010] The preparation method specifically comprises the following steps:
[0011] (1) coating a foaming mixed glue solution containing an acrylic resin solution on a PET release film, and then drying to remove the solvent at temperatures of 57-63° C., 67-73° C., 87-93° C., 97-103° C., 107-113° C., 107-113° C., and 97-103° C., with each temperature section lasting 20-40 seconds; after drying, laminating a silicone protective film to obtain a foaming glue film;
[0012] Preferably, the solvent is removed by drying at temperatures of 60°C, 70°C, 90°C, 100°C, 110°C, 110°C, and 100°C in sequence, with the drying time in each temperature section being 30 seconds.
[0013] (2) placing the film to be foamed at a temperature of 150-155° C. for foaming for 2-4 minutes to obtain acrylic acid adsorption foam;
[0014] Preferably, the foaming is carried out at a temperature of 150° C. for 3 minutes.
[0015] And / or, one side of the acrylic absorbent foam is a PET release film with a weight of 10-150 gf / inch; and the other side is a silicone protective film with a weight of 20-300 gf / inch.
[0016] The method for preparing the foaming mixed glue solution comprises the following steps:
[0017] (a) dissolving and mixing the second solvent, acrylic soft monomer, 1 / 2 acrylic functional monomer, and 0.1% by weight of the initiator of the total acrylic monomer, deoxygenating the mixture, reacting at 63-67° C. for 4-5 hours, then heating to 76±1° C. for 0.5-1.5 hours, adding acrylic hard monomer, the remaining acrylic functional monomer, the initiator, and the solvent mixture in batches, and continuing to heat to 80-82° C. for 4-6 hours to obtain an acrylic resin solution;
[0018] Preferably, first add 1 / 2 of the acrylic acid functional monomer into the reaction system, react at a temperature of 63-67°C for 4-5 hours, then heat to 76°C for 1 hour, then dropwise add the acrylic acid hard monomer, the remaining acrylic acid functional monomer, the initiator, and the solvent mixture, and continue to heat to 80-82°C for 5 hours.
[0019] Generally, free radical polymerization is considered successful if there is obvious viscosity and no other abnormalities in the system. In the present invention, the degree of reaction of acrylic acid free radical polymerization is monitored by measuring the solid content in the middle of the reaction. This reaction is relatively conventional and the condition can be judged by observing the viscosity with the naked eye.
[0020] (b) dispersing a chemical foaming agent, a curing agent, a nucleating agent, and a foam stabilizer in a first solvent, and then adding the acrylic resin solution obtained in step (a) and fully dispersing the mixture to obtain a foaming mixed glue solution.
[0021] In the above steps, the components in the foaming mixed glue solution are calculated by weight and include:
[0022]
[0023] The number average molecular weight of the acrylic resin in the acrylic resin solution is 400,000-2,000,000 g / mol, and the molecular weight distribution PDI is 2.0-7.0.
[0024] The chemical foaming agent is at least one of azodicarbonamides, hydrazine derivatives, semicarbazides, tetrazoles, nitroso compounds and carbonates; preferably at least one of SA5000D, OBSH series, TSH foaming agent, H foaming agent, low temperature H-1, SA3000, SA5000 of Shuntai Technology Company, Actmix ADC-75PE, Actmix-DPT of Ningbo Aikemu New Materials Company.
[0025] The curing agent is at least one of isocyanate, pyridine, amino resin and epoxy resin; preferably an active isocyanate curing agent: Covestro's N 3800, N3300, N 3900, XP 2763, XP 2838, XP 2489, XP 2847, L 75, XP 2617; the epoxy group resin is Mitsubishi Chemical's 11029-X, 11021-C, Hunstman's One of the GA-240.
[0026] The foam stabilizer is a highly active organic silicon surfactant with Si-C structure, preferably a polyether-modified siloxane.
[0027] The nucleating agent is at least one of talc, calcium carbonate, titanium dioxide, calcium oxide and calcium fluoride.
[0028] The first solvent is at least one of toluene, xylene, methylcyclohexane, cyclohexanone, methyl isobutyl ketone, butanone, ethyl acetate, butyl acetate and n-heptane.
[0029] In the above steps, the components in the acrylic resin solution, measured by weight, include:
[0030] Acrylic acid copolymer 100 parts;
[0031] 200-300 parts of the second solvent;
[0032] Preferably, the acrylic copolymer is obtained by free radical polymerization of acrylic monomers.
[0033] Specifically, the components in the acrylic resin solution include, by weight:
[0034]
[0035] Wherein, the acrylic iso-hard monomer is at least one of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate and lauryl (meth)acrylate.
[0036] The acrylic acid homopolymer monomer is at least one of ethyl acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate and isooctyl (meth)acrylate.
[0037] The acrylic functional monomer is at least one of (meth)acrylic acid, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, N-hydroxymethyl acrylamide, and ethyl acetoacetate.
[0038] The initiator is at least one of acyl peroxides, peroxycarboxylates, peroxydicarbonates and azo compounds; preferably at least one of benzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), dilauroyl peroxide (LPO), tert-amyl peroxy-2-ethylhexanoate (TAPO) and dihydroxycyclohexane peroxide (BHCP).
[0039] The second solvent is at least two of toluene, xylene, methylcyclohexane, ethyl acetate and butyl acetate.
[0040] An acrylic absorbent foam tape prepared by using the acrylic absorbent foam comprises acrylic absorbent foam, wherein one side of the absorbent foam having an open-pore structure is covered with double-sided adhesive, the double-sided adhesive substrate is PET, and both sides of the substrate are coated with acrylic adhesive.
[0041] That is, the foam tape comprises an acrylic absorbent foam layer, a polyester substrate layer attached to one side of the foam, and an acrylic pressure-sensitive adhesive layer attached to one side of the open-pore structure.
[0042] The preparation method of the foam tape is as follows: a substrate coated with acrylic adhesive on both sides is laminated to a surface of the absorbent foam having an open-pore structure, and after aging, an acrylic absorbent foam tape is obtained.
[0043] Beneficial effect: Since the material surface has a physical adsorption function rather than the traditional pressure-sensitive adhesive viscoelastic properties to provide the main anchoring force, the problem of the interface being difficult to peel off due to sufficient wetting and the influence of surface polarity factors can be avoided. Therefore, the present invention is based on the phenomenon that gas will overflow from the surface during chemical foaming, and the surface is covered with release films of different grammes or other forms of peelable protective films to provide a certain surface tension, which can effectively control the size of the bubbles formed by the bubbles overflowing from the foam surface, forming a foam surface layer that is mainly a semi-open-cell structure and a mainly closed-cell structure inside. While taking into account the temporary fixation and easy peeling requirements with physical adsorption function, it provides good impact resistance and cushioning performance, and can be reused. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] 1. Preparation of acrylic resin:
[0046] The raw materials are weighed according to the mass fractions, and the acrylic resin solution is prepared by dissolving and mixing the organic solvent, acrylic soft monomer, 1 / 2 acrylic functional monomer, and AIBN initiator accounting for 0.1% by mass of the monomers, bubbling for deoxygenation, adding into a glass reactor, heating to 63-67° C. for reaction for 4 hours, heating to 76° C. for reaction for 1 hour, and dropping all the remaining hard monomers, 1 / 2 acrylic functional monomer, BPO initiator accounting for 0.13% by mass of the monomers, and solvent mixture, and continuing to heat to 80-82° C. for reaction for 5 hours to obtain the acrylic resin solution.
[0047] Specifically, in this example, the hard monomer selected is methyl methacrylate (MMA), the soft monomer is isooctyl acrylate (2EHA), ethyl acrylate (EA), the functional monomer is acrylic acid (AA), hydroxyethyl acrylate (HEA), the thermal initiator is azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO), and the solvent is a mixture of ethyl acetate (EtAc) and toluene (Tol). The specific proportions of Example A-2 are shown in Table 1.
[0048] Table 1
[0049] Example 2EHA EA AA HEA MMA Etac TOI AIBN BPO <![CDATA[Mn(10* 4 )]]> PDI TG Solid A-2 35 35 4 1 25 75 75 0.1 0.13 40 2.33 -9.2 39.20%
[0050] Example A-1 is a commercially available adhesive, Anzuo Chemical: brand Y-1421 acrylic adhesive.
[0051] The acrylic resin in the specific embodiment was tested, and the test results are shown in Table 1:
[0052] (1) The glass transition temperature (TG) of acrylic resin was measured by DSC (differential scanning calorimeter) under the following conditions: temperature -50-200°C, heating rate 5°C / min, nitrogen protection 50 ml / min. Equipment model: DSC-800 (manufactured by the manufacturer).
[0053] (2) The molecular weight and molecular weight distribution width (Mn / PDI) of acrylic resin were measured by GPC (gel permeation chromatography), sample concentration: the sample was diluted to 1 mg / cm3 with tetrahydrofuran, mobile phase: tetrahydrofuran, flow rate: 1 cm3 / min, Agilent 1260 Infinity II GPC (manufactured by Agilent).
[0054] 2. Preparation of adsorbed acrylic foam tape:
[0055] Taking the solid mass parts of the acrylic resin solution obtained in Table 1 as 100 parts, the acrylic resin solution, chemical foaming agent, nucleating agent, surfactant, and solvent are mixed and dispersed at high speed using a planetary disperser, and finally a curing agent is added and dispersed at high speed uniformly, and a foaming solution is obtained after defoaming for standby use. Specific embodiments and comparative embodiments are shown in Table 2.
[0056] Table 2
[0057]
[0058] The curing agent in Table 2 is L 75, low surfactant is from Silok 2003, the chemical foaming agent is H foaming agent from Shuntai Technology Co., Ltd., and the nucleating agent is ultrafine calcium carbonate from Guangyuan Chemical.
[0059] Comparative Example 1: A-1 is the main resin coating liquid uniformly coated on the PET release film to obtain a dry adhesive film with a thickness of 75 μm.
[0060] In comparative example 2, the main resin coating liquid A-2 was uniformly coated on the PET release film to obtain a dry adhesive film with a thickness of 75 μm.
[0061] Comparative Example 3 and Examples 1-4 all use A-2 as the main resin to prepare acrylic acid adsorption foam:
[0062] (1) The foaming mixed adhesive solution is coated on a polyethylene glycol terephthalate (PET) release film, the PET release film has a gram weight of 50-75 gf / inch, and is placed in an oven to dry the solvent. The oven temperature is as follows: the first section oven temperature is 60°C; the second section oven temperature is 70°C; the third section oven temperature is 90°C; the fourth section oven temperature is 100°C; the fifth section oven temperature is 110°C; the sixth section oven temperature is 110°C; the seventh section oven temperature is 100°C. After drying, a silicone protective film is attached, the gram weight of which is 60-100 gf / inch, to obtain a sandwich structured adhesive film to be foamed.
[0063] (2) Place in an oven for high-temperature foaming at 150°C for 3 minutes to obtain acrylic foam.
[0064] (3) Tear off the obtained foam layer PET release film and stick it to the 15 μm thick side of the 12 μm PET substrate double-sided tape.
[0065] (4) The tape sample is aged and cross-linked at 60°C / 48h to obtain the final adsorbed acrylic foam tape.
[0066] The following are performance tests:
[0067] 1. 180° peel force test
[0068] The drop ball test method refers to the national standard (ASTM / D3330).
[0069] Remove the acrylic adhesive layer, use the 25μm PET original film as the backing reinforcement film, and test the SUS substrate. Use a pressure roller during the lamination process to avoid bubbles. Place the sample at room temperature and humidity for 72 hours (temperature 23℃±2, humidity 50%±5) to complete the sample preparation.
[0070] After standing still, fix the test plate on the tensile testing machine, bend the lower part of the test piece 180°, fix it on the chuck above, and peel it at a speed of 300mm / min. The peeling length is more than 100mm. The average force value of 25-75% of the peeling distance is used as the peeling force, which is converted into peeling strength.
[0071] 2. T-block
[0072] The sample size is 25mm*25mm. Remove the release film on one side of the sample and stick the adhesive surface to the sticking plane of a T-shaped fixture. Note that no air should be left on the sticking surface during the bonding process. After completion, remove the release film on the remaining side of the sample and use the same method to stick the adhesive surface to the second T-shaped fixture. Apply a 110N pressing force on both sides of the two T-shaped fixtures that have been pasted through the sample for 10 seconds to ensure full bonding. Place the sample at room temperature and humidity for 72 hours (temperature 23℃±2, humidity 50%±5) to complete the sample preparation.
[0073] After standing still, the two T-shaped fixtures are connected to the bottom fixed end and the top hook of the tensile testing machine respectively, and the tensile testing machine is turned on under the test environment with a stretching rate of 300mm / min until the two T-shaped fixtures are completely disengaged.
[0074] According to the above evaluation method, the test results of the foam tape samples are shown in Table 3 below:
[0075] Table 3 Sample performance test results
[0076]
[0077] Note: In the table, O: excellent; ▲: average; X: poor.
[0078] In summary, after the sandwich structure of release film / resin / silicone protective film is foamed, a large number of regular semi-open cells are formed on the surface of the foam, which is similar to the suction cup structure, and can effectively increase the adsorption force of the material to the smooth material. The non-traditional pressure-sensitive adhesive infiltration and anchoring effect can achieve easy peeling at a certain angle.
[0079] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. An acrylic acid adsorption foam, characterized in that: At least one side surface of the adsorption foam has an open-pore structure.
2. The acrylic acid adsorption foam according to claim 1, characterized in that: The open-pore structure is a semi-open-pore structure.
3. The method for preparing the acrylic acid adsorption foam according to claim 1 or 2, characterized in that: The method comprises the steps of using a foaming mixed glue solution containing an acrylic resin solution as a foaming substrate and preparing an adsorbent foam by a chemical foaming method, wherein before the chemical foaming, the method further comprises the step of coating the foaming mixed glue solution on a peelable protective film; Preferably, the peelable protective film is a PET release film.
4. The method for preparing the acrylic acid adsorption foam according to claim 1 or 2, characterized in that: The specific steps include: (1) coating a foaming mixed glue solution containing an acrylic resin solution on a PET release film, and then drying to remove the solvent at temperatures of 57-63° C., 67-73° C., 87-93° C., 97-103° C., 107-113° C., 107-113° C., and 97-103° C., with each temperature section lasting 20-40 seconds, and laminating a silicone protective film after drying to obtain a foaming glue film; (2) placing the film to be foamed at a temperature of 150-155° C. for foaming for 2-4 minutes to obtain acrylic acid adsorption foam; And / or, one side of the acrylic absorbent foam is a PET release film with a gram weight of 10-150 gf / inch; and the other side is a silicone protective film with a gram weight of 20-300 gf / inch.
5. The preparation method according to claim 3 or 4, characterized in that: The preparation method of the foaming mixed glue solution comprises the following steps: (a) dissolving and mixing the second solvent, acrylic soft monomer, part of acrylic functional monomer, and 0.1% by weight of the initiator of the total acrylic monomer, deoxygenating, reacting at a temperature of 63-67° C. for 4-5 hours until a significant viscosity is obtained, then heating to 75-77° C. for 0.5-1.5 hours, adding acrylic hard monomer, the remaining acrylic functional monomer, the initiator, and the solvent mixture in batches, and continuing to heat to 80-82° C. for about 4-6 hours to obtain an acrylic resin solution; (b) dispersing a chemical foaming agent, a curing agent, a nucleating agent, and a foam stabilizer in a first solvent, and then adding the acrylic resin solution obtained in step (a) and fully dispersing the mixture to obtain a foaming mixed glue solution.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The components in the foaming mixed glue solution are measured by weight and include: The number average molecular weight of the acrylic resin in the acrylic resin solution is 400000-2000000 g / mol, and the molecular weight distribution PDI is 2.0-7.0; Preferably, the chemical foaming agent is at least one of azodicarbonamides, hydrazine derivatives, semicarbazides, tetrazoles, nitroso compounds and carbonates; Preferably, the curing agent is at least one of isocyanates, pyridines, amino resins and epoxy resins; Preferably, the foam stabilizer is a highly active organosilicon surfactant with a Si-C structure; Preferably, the nucleating agent is at least one of talc, calcium carbonate, titanium dioxide, calcium oxide and calcium fluoride.
7. The preparation method according to any one of claims 3 to 5, characterized in that: The components in the acrylic resin solution are measured by weight and include: Acrylic acid copolymer 100 parts; 100-300 parts of the second solvent; Preferably, the acrylic copolymer is obtained by free radical polymerization of acrylic monomers.
8. The preparation method according to claim 7, characterized in that: The components in the acrylic resin solution are measured by weight and include: Preferably, the initiator is at least one of acyl peroxides, peroxycarboxylates, peroxydicarbonates and azo compounds.
9. An acrylic absorbent foam tape, characterized in that: It comprises the acrylic adsorption foam as claimed in claim 1 or 2, wherein one side of the adsorption foam having an open-pore structure is covered with double-sided adhesive; And / or, the foam tape comprises an acrylic absorbent foam layer, a polyester substrate layer attached to one side of the foam, and an acrylic pressure-sensitive adhesive layer attached to the other side; Preferably, the double-sided adhesive substrate is PET, and both sides of the substrate are coated with acrylic adhesive.
10. The method for preparing the acrylic acid absorption foam tape according to claim 8, characterized in that: The PET substrate coated with acrylic adhesive on both sides is laminated to the side of the absorbent foam with an open-pore structure, and after aging, an acrylic absorbent foam tape is obtained.